Research and Development in the Philippine Fisheries Sector - Danilo C. Israel (Philippine Institute for Development Studies (PIDS), 1999)
This paper reviews the status of R&D in the Philippine fisheries sector and identifies the problems it is facing. It finds that fisheries R&D is generally ineffective as it is beset by many institutional, capability and management problems. The paper suggests certain concrete actions which need to be done to address the problems including the streamlining of the bureaucracy and the infusion of more R&D funds as promised by the Philippine Fisheries Code and AFMA.
Keywords: 330; fisheries sector; research and development sector